2011
DOI: 10.1073/pnas.1102241108
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimerization of Mdm2 and Mdm4 is critical for regulating p53 activity during embryogenesis but dispensable for p53 and Mdm2 stability

Abstract: Mdm2 and Mdm4 are homologous RING domain-containing proteins that negatively regulate the tumor suppressor p53 under physiological and stress conditions. The RING domain of Mdm2 encodes an E3-ubiquitin ligase that promotes p53 degradation. In addition, Mdm2 and Mdm4 interact through their respective RING domains. The in vivo significance of Mdm2-Mdm4 heterodimerization in regulation of p53 function is unknown. In this study, we generated an Mdm4 conditional allele lacking the RING domain to investigate its rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(169 citation statements)
references
References 37 publications
7
162
0
Order By: Relevance
“…We validated this notion by measuring the level of MDMX transcripts in MCF-7 cells treated with NRG1 at different time points (6,12, and 24 h). The result showed no statistically significant difference in MDMX mRNA levels after NRG1 treatment at any of the time points (Fig.…”
Section: Her4 Overexpression Stabilizes the Mdmx-mdm2 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…We validated this notion by measuring the level of MDMX transcripts in MCF-7 cells treated with NRG1 at different time points (6,12, and 24 h). The result showed no statistically significant difference in MDMX mRNA levels after NRG1 treatment at any of the time points (Fig.…”
Section: Her4 Overexpression Stabilizes the Mdmx-mdm2 Complexmentioning
confidence: 99%
“…In fact, the MDMX-MDM2 heterocomplex is the main form in which the two proteins are found in the cell (10,11), and loss of this formation leads to p53 activation and embryonic lethality (9,(11)(12)(13).…”
mentioning
confidence: 99%
“…Human Pla2g16: forward primer CCAGGTCAACAACAAACATGATG; reverse primer CCCGCTGGATGATTTTGC. GAPDH or RPLP0 genes were used as quantitative RT-PCR (qRT-PCR) internal controls (37). The murine p53 knockdown plasmid was reported previously (38).…”
Section: Methodsmentioning
confidence: 99%
“…The rescue of Mdm4 knockout and Mdm4 RING domain mutant mice by p53 deficiency concluded that Mdm4 has a non-overlapping function of Mdm4 with Mdm2. 12,13,19 However, this conclusion is difficult to reconcile with the finding that an Mdm2 transgene containing Mdm2 gene and its native promotor can completely rescue Mdm4-deficiency-induced p53-dependent lethality, leading to a conclusion that Mdm2 and Mdm4 are functionally overlapping in development. 28 Based on our biochemical model, it is higly likely that the Mdm2 splice isoforms expressed from the Mdm2 transgene, rather than the overexpression of full-length Mdm2 per se, may have compensated for the loss of Mdm4 as a RING-domain stimulater of full length Mdm2 activity to fully suppress p53 during development.…”
Section: Mdm2 Isoforms Are Super Active E3 Ligase For Ubiquitination mentioning
confidence: 99%
“…10 Mouse genetics studies indicated that RING-RING interaction of Mdm2-Mdm4 domain is essential for restricting p53 activity during embryonic development, since mutation of either Mdm2 or Mdm4 RING domain causes p53-dependent embryonic lethality. [11][12][13] Mdm2 alternative splice isoforms were reported years ago. 14 Two major splice isoforms Mdm2-A and Mdm2-B (referred thereafter as Mdm2-A/B) do not bind to p53 and induce p53-independent cell growth in vivo and tumorigenesis in vivo.…”
Section: Introductionmentioning
confidence: 99%